2000
DOI: 10.1097/00006565-200010000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Transferring patients to a pediatric trauma center: The transferring hospital’s perspective

Abstract: The rationale behind a regionalized trauma system is that patient outcomes are improved when trauma patients are rapidly transported to facilities with the level of expertise need to treat their injury. Functioning as an adult Level II trauma center, we wanted to know how the transfer process worked for pediatric patients whom we transfer to a Level I pediatric trauma center, which is part of the same multihospital system. Complete information on time of arrival, the time the transfer was accepted, and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Previous studies of transferred trauma patients have found shorter intervals than we found, with the time from presentation at the referring hospital until transfer request ranging from 62 to 78 min and the time spent at the referring hospital taking 182 min (17)(18)(19)(20)(21). Differences among these results underscore the inherent variability of the interhospital transfer process in different trauma systems.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies of transferred trauma patients have found shorter intervals than we found, with the time from presentation at the referring hospital until transfer request ranging from 62 to 78 min and the time spent at the referring hospital taking 182 min (17)(18)(19)(20)(21). Differences among these results underscore the inherent variability of the interhospital transfer process in different trauma systems.…”
Section: Discussioncontrasting
confidence: 59%
“…In Australia, system inefficiencies have been associated with delayed transfer that result in longer ED length of stay (LOS) and increased workloads when arranging an IHT . Similar issues have also been noted elsewhere . However, few studies have examined process issues when arranging IHT, particularly from the perspective of the referring hospital ED.…”
Section: Introductionmentioning
confidence: 99%
“…1 Similar issues have also been noted else-where. 3,4 However, few studies have examined process issues when arranging IHT, particularly from the perspective of the referring hospital ED.…”
Section: Introductionmentioning
confidence: 99%
“…12 Transfer is not without risks, and inadequate handoff communication, poor selection for transfer, transport risk, and cost all threaten to diminish the benefits if transfer is applied indiscriminately. [13][14][15] Patients cite significant concerns with the transfer process and report that interhospital transfer can be unpredictable, scary, confusing, and stressful. 16,17 Furthermore, some physician opinions regarding patient preferences are discordant with patients' selfreported preferences.…”
mentioning
confidence: 99%
“…Objective patient outcomes are improved in high‐volume regional centers supported by networks targeting specific diseases, but some conditions still suffer from overtriage . Transfer is not without risks, and inadequate handoff communication, poor selection for transfer, transport risk, and cost all threaten to diminish the benefits if transfer is applied indiscriminately . Patients cite significant concerns with the transfer process and report that interhospital transfer can be unpredictable, scary, confusing, and stressful …”
mentioning
confidence: 99%